Polymorphisms of genes coding for ghrelin and its receptor in relation to anthropometry, circulating levels of IGF-I and IGFBP-3, and breast cancer risk: a case-control study nested within the European Prospective Investigation into Cancer and Nutrition (EPIC). - Dossus, L; McKay, J; Canzian, F; Wilkening, S; Rinaldi, S; Biessy, C; Olsen, A; Tjønneland, A; Jakobsen, M; Overvad, K; Clavel-Chapelon, F; Boutron-Ruault, M; et al. (2008)
Ghrelin, an endogenous ligand for the growth hormone secretagogue receptor, has two major functions: the stimulation of the growth hormone production and the stimulation of food intake. Accumulating evidence also suggests a role of ghrelin in cancer development. We conducted a case-control study on 1359 breast cancer cases and 2389 matched controls, nested within the European Prospective Investigation into Cancer and Nutrition, to examine the association of common genetic variants in the genes coding for ghrelin (GHRL) and its receptor (GHSR) with anthropometric measures, circulating insulin growth factor I (IGF-I) and insulin-like growth factor-binding protein 3 and breast cancer risk. Pair-wise tagging was used to select the 15 polymorphisms that represent the majority of common genetic variants across the GHRL and GHSR genes. A significant increase in breast cancer risk was observed in carriers of the GHRL rs171407-G allele (odds ratio: 1.2; 95% confidence interval: 1.0-1.4; P = 0.02). The GHRL single-nucleotide polymorphism rs375577 was associated with a 5% increase in IGF-I levels (P = 0.01). A number of GHRL and GHSR polymorphisms were associated with body mass index (BMI) and height (P between <0.01 and 0.04). The false-positive report probability (FPRP) approach suggests that these results are noteworthy (FPRP < 0.20). The results presented here add to a growing body of evidence that GHRL variations are associated with BMI. Furthermore, we have observed evidence for association of GHRL polymorphisms with circulating IGF-I levels and with breast cancer risk. These associations, however, might also be due to chance findings and further large studies are needed to confirm our results.